Characterization of Axillary Lymph Nodes Using Conventional Ultrasonography Compared with Histopathological Findings - Farhana, Irin; Alam, Sayed Zoherul; Raisul, Md Nurul Islam; Islam, Zahirul (Community Based Medical Journal, 2024)
A cross-sectional, observational study was carried out the Department of Radiology and Imaging, Combined Military Hospital (CMH) at Dhaka Cantonment, Bangladesh, between March and August of 2021. A total of 75 female patients were included presenting with or without axillary swelling referred for ultrasound of breasts and axilla from various surgical and medical departments of the same hospital. B-mode ultrasonography was used as method of choice because of its noninvasiveness and availability in evaluating the axillary lymph nodes. Histopathological diagnosis was considered the gold standard for the diagnosis. The average age was 42.62±8.76 years. In conventional ultrasonography results, 33.3% were benign lymph node, 14.7% were reactive and 52% were metastatic lymph node. Based on the histopathological reports, lymph node involvement was detected in 18(24%) patients with benign, 13(17.3%) patients reactive and 44(58.7%) metastatic. The overall results revealed 79.5% sensitivity, 87.1% specificity, 89.7% PPV and 75% NPV. To summarize, conventional ultrasonography was moderately sensitive with good specificity for diagnosis of axillary lymph node. Further studies with a larger population and intra-operative axillary lymph node are recommended. CBMJ 2024 January: vol. 13 no. 01 P: 3-8